Biomechanical analysis of ankle kinematics and ligament strain in snowboarding - Delorme, Sebastien (University of Ottawa (Canada), 2004)
Because snowboarders are known to injure their ankles more often than alpine skiers, it has been postulated that stiffer snowboard boots would provide better protection to the ankle ligaments than current soft boots do. To test this hypothesis, we have measured the kinematics of the feet and lower legs of five snowboarders riding down a course of 10 gates on a ski hill using an electromagnetic motion tracking system. Results were obtained with each snowboarder wearing soft boots and stiffer step-in boots. The measurements were expressed in anatomically relevant rotations of the ankle joint complex. Two models were developed to predict ligament strains from rotations of the ankle joint complex: (1) a statistical model using published ligament strain measured on cadaver specimens at various combinations of ankle rotations as an interpolation and extrapolation table to predict strains in two ankle ligaments at the rotations measured during the snowboarding trials; (2) a personalized 2-degrees-of-freedom kinematic model of the ankle joint complex, based on the Denavit-Hartenberg formulation of serial-link manipulators, to predict strains in flue ankle ligaments from the relative position of the shank and foot. The experimental results showed that the left and right ankles are asymmetrically rotated, mostly in dorsiflexion, eversion and external rotation. Compared to step-in boots and bindings, soft boots and strap bindings allowed more rotation of the ankle joint complex and more strain in the anterior talofibular ligament, according to the statistical model. The kinematic model was not sensitive enough to detect differences in ligament strains between the 2 types of equipment. A functional determination of the axes of rotation of the talocrural and subtalar joints could further improve the predictions of this model. This is the first known study to document experimentally the kinematics of snowboarding. It generally confirms the expectation that softer boats allow significantly wider ranges of ankle rotation and ligament strain.
Keywords: Engineering, Biomedical.; Biophysics, Medical.